Localization of partial discharge in transformer oil using Fabry-Pérot optical fiber sensor array - Gao, Chaofei; Wang, Wei; Song, Shu; Wang, Shijie; Yu, Lei; Wang, Yangchao (IEEE transactions on dielectrics and electrical insulation, 2018)
Partial discharge is the main reason for insulation deterioration and failure of high voltage electrical asset. Thus, the online detection and localization of partial discharge can provide the information on the equipment degradation characteristics, and moreover, is of great value for improving the safe operation of the power grid and the developing of optimal maintenance. Accounting for the good sensitivity, the high immunity to electromagnetic interference, the compact size with outstanding insulation level, the Fabry-Pérot optical fiber sensor is attracting increasing attention as a promising way for online acoustic partial discharge localization. In this study, the partial discharge localization in the transformer oil is realized by an ultrasonic detection system, which is consisting of 2×2 Fabry-Pérot optical fiber sensor array with steered response power algorithm. In general, the Fabry-Pérot optical fiber acoustic sensor array shows good direction sharpness, and achieves accurate localization. This detection and localization system is further applied to a 35 kV transformer single-phase winding and verified with partial discharges on the outer winding.